Safety and Effectiveness of Percutaneous Low-Dose Thrombin Injection for Femoral Puncture Site Pseudoaneurysms in Neurointervention: Single-Center Experience - Jae Ho Shin; Yunsun Song; Jae Jon Sheen; Dongwhane Lee; Jaewoo Chung; Ga Young Lee; Hyunhee Jeong; Seongsik Han; Joon Ho Choi; Seon Moon Hwang; Deok Hee Lee (Neurointervention, 2020)
Purpose We present ultrasound-guided percutaneous low-dose thrombin (200–250 IU) injection for the treatment of iatrogenic femoral pseudoaneurysms. Second, we compared patient and procedure factors between subcutaneous hematoma and pseudoaneurysm groups.Materials and Methods From April 2012 to May 2018, 8,425 patients underwent neurointervention. Among these patients, 18 had small subcutaneous hematomas and 6 had pseudoaneurysms. Pseudoaneurysms in the neck and entire sac were visualized, and low-dose thrombins were injected while visualizing a “whirlpool” hyperechoic core in the pseudoaneurysm sac. Subcutaneous hematomas were treated with simple compression. We compared the following parameters between the subcutaneous hematoma group and pseudoaneurysm group: sex, age, body mass index (BMI), type of procedure, heparin usage, sheath size, procedure time, and number of previous neurointervention procedures with the Mann-Whitney U test. Results Most of the pseudoaneurysms were successfully occluded with 200 IU of thrombin (n=5). Only 1 pseudoaneurysm required a slightly higher thrombin concentration (250 IU, n=1). During the short-term follow-up, no residual sac was observed and no surgical repair was necessary. Pain in the groin region was alleviated. During the 1-month follow-up, no evidence of pseudoaneurysm recurrence nor subcutaneous hematoma was noted. Patient factors (sex, age, and BMI) and procedure factors (heparin usage, sheath size, procedure time, number of previous procedures) were not statistically different between the subcutaneous hematoma and pseudoaneurysm groups. Conclusion Ultrasound-guided percutaneous low-dose thrombin injection (200–250 IU) is safe, effective, and less invasive for treating iatrogenic femoral pseudoaneurysm in neurointervention.